Academic Flying and the Means of Communication - Bjørkdahl, Kristian; Franco Duharte, Adrian Santiago (Springer Nature, 2022)
This open access book shines a light on how and why academic work became entwined with air travel, and what can be done to change academia’s flying habit. The starting point of the book is that flying is only one means of scholarly communication among many, and that the state of the planet now obliges us to shift to other means. How can the academic-as-globetrotter become a thing of the past? The chapters in this book respond to this call in three steps. It documents the consequences of academic flying, it investigates the issue of why academics fly, and it begins an effort to think through what can replace flying, and how. Finally, it confronts scholars and scientists, students, activists, research funders, university administrators, and others, with a call to translate this research into action.